Hong Kong Culture and Society in the New Millennium : Hong Kong as Method - Chu, Yiu-Wai (Springer Singapore : Imprint: Springer, 2017)
This book discusses the notion of "Hong Kong as Method" as it relates to the rise of China in the context of Asianization. It explores new Hong Kong imaginaries with regard to the complex relationship between the local, the national and the global. The major theoretical thrust of the book is to address the reconfiguration of Hong Kong's culture and society in an age of global modernity from the standpoints of different disciplines, exploring the possibilities of approaching Hong Kong as a method. Through critical inquiries into different fields related to Hong Kong's culture and society, including gender, resistance and minorities, various perspectives on the country's culture and society can be re-assessed. New directions and guidelines related to Hong Kong are also presented, offering a unique resource for researchers and students in the fields of cultural studies, media studies, postcolonial studies, globalization and Asian studies.
Keywords: Social sciences.; Culture -- Study and teaching.; Cultural studies.; elektronické knihy; electronic books